PENERAPAN PROTOKOL KESEHATAN DALAM PEMBELAJARAN TATAP MUKA PADA MASA ERA NEW NORMAL DI PAUD PLUS DARUSSALAM BOJONEGORO - Nurul Novitasarii; Siti Istiqomah' (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2021)
This research was conducted with the aim of knowing the application of health protocols in the new normal era in PAUD Plus Darussalam Bojonegoro. The research method used in this research is descriptive qualitative. Data collection techniques obtained through observation, interviews and documentation, related to the implementation of health protocols during the pandemic in PAUD plus Darussalam Bojonegoro. The informants in this study were the principal, teachers and parents at PAUD Plus Darussalam Bojonegoro. The findings in this study are the application of health protocols in the new normal era in PAUD Plus Darussalam Bojonegoro including: availability of health protocol facilities such as hand washing stations, spraying disinfectant liquid throughout the school area, spraying steam disinfectant to teachers and students, 2) Regulation of facilities and infrastructure such as: learning divided into 2 shifts, learning a maximum of 2 hours, and 3) learning activities by keeping a distance, always using a mask / face shield.